Anterior cervical Corpectomy with cage and plating in subaxial fractures: A review of 20 cases. - Mohamed Amer (Egyptian Spine Association, 2013)
Background Data: Anterior cervical corpectomy was the best solution in some cases of subaxial fracture but this defect was a problem to fill after corpectomy, so this study was to show the efficacy and safety of carbon cage and plating in the treatment of this problem. Study Design: A clinical case series review Purpose: To review the safety, efficacy and outcome of anterior cervical corpectomy with cage and plating in the management of subaxial cervical fractures. Patients and Methods: From January 2009 to January 2014, twenty patients underwent anterior cervical corpectomy with cage and plating for the treatment of subaxial spinal injuries. The functional status was assessed using the modified Japanese Orthopedic Association Score preoperatively and at 1, 3 and 6 months postoperatively. Radiological assessment was done preoperatively with MRI, CT scan and plain radiograph, and at 1, 3 and 6 months postoperativelyby plain radiograph and CT scan. Results: Patients’ ages ranged from 17 to 60 years (mean 38.5 years); 14 patients were males. Fourteen patients underwent one-level corpectomy and six patients underwent two-level corpectomy. Of our 20 patients; 16 patients (80%) had satisfactory significant recovery (one point or more on (mJOA) score), while four patients (20%) had no clinical improvement (same preoperative points on (mJOA) score). There was no case of cervical instability, instrument break down, or fusion failure during follow up period. Conclusion: The anterior cervical corpectomy with cage and plating is a safe and effective technique in subaxial spinal injuries in selected patients. (2013ESJ057)